Pengaruh Kecerdasan Emosional dan Motivasi Belajar terhadao Prestasi Belajar IPA Siswa Kelas VIII SMPN 4 Ruteng-Lengor - Maria Septelniati Seko; An Nisaa Al Mu’min Liu; Maimunah H Daud (Edumaspul: Jurnal Pendidikan, 2022)
This research aims: (1) to find out the influence of emotional intelligence on the learning achievement of students of class VIII SMPN 4 Ruteng, (2) to find out the influence of learning motivation on the learning achievement of students of class VIII SMPN 4 Ruteng, (3) to know the influence of emotional intelligence and learning motivation on the achievement of students of class VIII SMPN 4 Ruteng-Lengor school year 2020/2021.The type of research used is quantitative research with ex post facto research design. The population in this study were all students of class VIII SMPN 4 Ruteng-Lengor totaling 100 people and the research sample amounting to 80 people obtained using simple random sampling technique. Data collection techniques using questionnaires and documentation. Questionnaire to measure emotional intelligence and learning motivation, while documenting student report cards for the even semester of the 2020/2021 academic year for learning achievement. Data analysis used normality test, linearity test, multicollinearity test, heteroscedasticity test, simple regression analysis and multiple regression analysis. The results of the study show that: first, there is a significant influence between emotional intelligence on science learning achievement for class VIII students of SMPN 4 Ruteng-Lengor for the academic year 2020/2021. This is evidenced by a simple regression test obtained the magnitude of 0.00 <0.05. Second, there is a significant influence between learning motivation on science learning achievement for class VIII students of SMPN 4 Ruteng-Lengor for the 2020/2021 academic year. This is evidenced by a simple regression test obtained the magnitude of 0.03 <0.05. Third, there is a significant influence between emotional intelligence and learning motivation on the science learning achievement of class VIII students of SMPN 4 Ruteng-Lengor for the 2020/2021 academic year. This is evidenced by the multiple regression test obtained the magnitude of 0.00 <0.05.